(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2021)
Throughout its history, Dialectology and Geolinguistics have sought to establish boundaries or borders based on facts of the language in order to be able to define and distinguish some dialects from others. Linguistic Geography deals with how languages are presented in space, establishing isoglosses, boundaries, borders and transition areas; it deals also with issues related to languages in contact, both in the present and in the past. This article analyzes the controversy surrounding the term "linguistic boundary" and delves into one of the least studied linguistic boundaries of Spanish: the southern area of Castile-La Mancha.